AB205. SOH26AB_0192. Pancreatectomy for metastatic renal cell carcinoma: a case series of 11 patients from a tertiary centre - Clercq, Nina Carlos-De; O’Brien, Stephen; Hayes, Brian; Súilleabháin, Criostóir Ó; O’Sullivan, Adrian (Mesentery and Peritoneum, 2026)
Pancreatic metastases account for only 2–5% of malignant pancreatic lesions, with renal cell carcinoma (RCC) being the most common primary source. Current guidelines support metastasectomy for oligometastatic disease following multidisciplinary team (MDT) review. This study presents an Irish case series evaluating outcomes following pancreatectomy for metastatic RCC.